Komplikasi Kardiovaskular dan Neurologis yang Berhubungan dengan Fibrilasi Atrium - Raymond Pranata; Hadrian Deka; Bambang Budi Siswanto (The Indonesian Heart Association, 2016)
Atrial fibrillation (FA) is the most common type of sustained-arrhythmia and one of the leading causes of mortality and morbidity globally, with estimated five million incidents. FA was associated with increased all-cause mortality (RR 1.46), cardiovascular mortality (RR 2.03), major cardiovascular events (RR 1.96), stroke (RR 2.42), ischemic stroke (RR 2.33), dementia (HR 1.42) and cognitive decline, ischemic heart disease (RR 1.61), sudden cardiac death (RR 1.88), heart failure (RR 4.99), chronic kidney disease (RR 1.64), and peripheral artery disease (RR 1.31). Overall, all-cause and cardiovascular mortality increased. Cognitive decline and dementia are also a concern since they impair function and quality of life. Overall, FA has bidirectional association with other cardiovascular diseases hence it acts as a marker for them. Therefore, prevention and control of risk factors are of utmost importance.